Ocorrência de domácias em espécies e híbridos da Família Vitaceae - Barros, Myrthes Apparecida Adâmoli de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1963)
The paper deals with the ocurrence of domatia in species and hybrids of Vitaceae family. The author found domaãtia in 95 of 157 hybrids studied. The domatia are always in the axils of the first and second ribs, and occasionaly also in ribs of others orders. The domatia found were of the types: "en touffe de poils", "en pertuis" and "en pochette", types according to the Chevalier's Classification (1941). It was found a varation of the type "en pertuis", the hole being not circular but narrow and long. One of the hybrids have domatia of two types: "en touffe de pois" and "en pertuis". Many of the domatia have mites in its interior.